Leishmanicidal Activity of Piper nigrum Bioactive Fractions is Interceded via Apoptosis In Vitro and Substantiated by Th1 Immunostimulatory Potential In Vivo - Chouhan, Garima; Islamuddin, Mohammad; Want, Muzamil Y.; Ozbak, Hani A.; Hemeg, Hassan A.; Sahal, Dinkar; Afrin, Farhat (Frontiers in Microbiology, 2015)
VL is a life-threatening protozoal infection chiefly impinging the rural and poor population in the tropical and sub-tropical countries. The deadly affliction is rapidly expanding after its association with AIDS, swiftly defying its status of a neglected disease. Despite successful formulation of vaccine against canine leishmaniasis, no licensed vaccine is yet available for human VL, chemotherapy is in appalling state, and the development of new candidate drugs has been painfully slow. In face of lack of proper incentives, immunostimulatory plant preparations owing antileishmanial efficacy bear potential to rejuvenate awful antileishmanial chemotherapy. We have earlier reported profound leishmanicidal activity of P. nigrum seeds hexane (PNH) and P. nigrum ethanolic (PNE) fractions derived from P. nigrum seeds against Leishmania donovani promastigotes and amastigotes. In the present study, we illustrate that the remarkable anti-promastigote activity exhibited by PNH and PNE is mediated via apoptosis as evidenced by phosphatidylserine externalization, DNA fragmentation, arrest in sub G0/G1 phase, loss of mitochondrial membrane potential and generation of reactive oxygen species. Further, P. nigrum bioactive fractions rendered significant protection to L. donovani infected BALB/c mice in comparison to piperine, a known compound present in Piper species. The substantial therapeutic potential of PNH and PNE was accompanied by elicitation of cell-mediated immune response. The bioactive fractions elevated the secretion of Th1 (INF-γ, TNF-α and IL-2) cytokines and declined IL-4 and IL-10. PNH and PNE enhanced the production of IgG2a, upregulated the expression of co-stimulatory molecules CD80 and CD86, augmented splenic CD4+ and CD8+ T cell population, induced strong lymphoproliferative and DTH responses and partially stimulated NO production. PNH and PNE were devoid of any hepatic or renal toxicity. These encouraging findings merit further exploration of P. nigrum bioactive fractions as a source of potent and non-toxic antileishmanials.